RETRACTED: PENGEMBANGAN DESAIN MOTIF BATIK REYOG BULKIYO DALAM MENDUKUNG DESA WISATA KEMLOKO, KECAMATAN NGLEGOK, KABUPATEN BLITAR - Nurul Ratnawati; I Nyoman Ruja; Agung Wiradimadja; Ferdinan Bashofi (Universitas Negeri Malang, 2022)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Praksis dan Dedikasi Sosial to article entitle “Pengembangan Desain Motif Batik Reyog Bulkiyo dalam Mendukung Desa Wisata Kemloko, Kecamatan Nglegok, Kabupaten Blitar” Vol. 5, No. 1 (2022), DOI: http://dx.doi.org/10.17977/um032v5i1p46-53.This paper has been found to be in violation of the Jurnal Praksis dan Dedikasi Sosial publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Jurnal Praksis dan Dedikasi Sosial, Vol. 4, No. 2 (2021), DOI: http://dx.doi.org/10.17977/um032v4i2p55-61.The document and its content has been removed from Jurnal Praksis dan Dedikasi Sosial and a reasonable effort should be made to remove all references to this article.